2018
DOI: 10.3389/fnsyn.2018.00019
|View full text |Cite
|
Sign up to set email alerts
|

hsa-let-7c miRNA Regulates Synaptic and Neuronal Function in Human Neurons

Abstract: Non-coding RNA, including microRNA (miRNA) serves critical regulatory functions in the developing brain. The let-7 family of miRNAs has been shown to regulate neuronal differentiation, neural subtype specification, and synapse formation in animal models. However, the regulatory role of human let-7c (hsa-let-7c) in human neuronal development has yet to be examined. Let-7c is encoded on chromosome 21 in humans and therefore may be overexpressed in human brains in Trisomy 21 (T21), a complex neurodevelopmental di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…In addition, a number of miRNAs have been shown to be involved in synapses and may participate in the regulation of synaptic development, as well as functional regulation (42). A previous study reported that miR-134-5p is involved in the development and morphological changes of synapses (43). miR-134 is found in neurons and dendrites of primary cultured neurons, where it regulates the development of the dendritic spine by targeting LimK1 mRNA, which can be inhibited by BDNF (18).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a number of miRNAs have been shown to be involved in synapses and may participate in the regulation of synaptic development, as well as functional regulation (42). A previous study reported that miR-134-5p is involved in the development and morphological changes of synapses (43). miR-134 is found in neurons and dendrites of primary cultured neurons, where it regulates the development of the dendritic spine by targeting LimK1 mRNA, which can be inhibited by BDNF (18).…”
Section: Discussionmentioning
confidence: 99%
“…miR-let-7e expression was strongly correlated with the development of EAE symptoms (31). In addition, miRNAs of the let-7 family have been described several times in various studies in the context of neurogenesis and axonal guidance (58,60,74,94,101). MiRlet-7 was described in conjunction with neurodegenerative processes (45,80).…”
Section: Potential Targets Of Dysregulated Mirnas In Gm-ms-lesionsmentioning
confidence: 99%
“…Interestingly, the occurrence in neurons has been described for the miRNAs miR-330 (14) and miR574 (49) and some miRNAs of the let-7 family (58,60,74,94,101).…”
Section: Six Mirnas Show Stronger Upregulation In Gm Lesions Than In mentioning
confidence: 99%
“…The copyright holder for this preprint this version posted October 27, 2020. ; https://doi.org/10.1101/2020.10.24.20218677 doi: medRxiv preprint neurodegeneration (15), and neurodevelopmental disorders (10). while DS and AD have been found to have robust associations to dyslipidemias, particularly low HDL-Col concentration, common conditions in DS patients (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%